Cave deposits in contemporary Polish sightseeing: social awareness of this issue - Krajcarz, Maciej T. (Turystyka i krajoznawstwo, 2021)
Caves play an important role in tourist sightseeing. Some of them are eagerly visited by tourists due to the beautiful speleothems, the opportunity to see bats, the charm of underground passages and the aura of mystery. From the academic point of view, a particularly important element of caves is their deposits – the series of clastic sediments filling a cave cavity. They constitute an important source of information about the history and prehistory of human settlement in caves and their surroundings, and also the history of fauna and flora, the geological processes responsible for the accumulation of sediments and climate change. In this study, an evaluation of the importance of cave deposits to cave tourism is attempted, whether the Polish term „namulisko” (cave deposits) itself or the idea it expresses, is known in the public, and also how cave deposits are perceived by tourists, if at all, and which aspects are known. There was an attempt at recognition of this among tourists in the context of their general knowledge about caves. The research was carried out using anonymous questionnaires distributed among various social groups such as school and university students, teachers and tourists.